WAYS TO IMPROVE THE TECHNIQUE OF TEACHING HISTOLOGY, CYTOLOGY AND EMBRYOLOGY FOREIGN STUDENTS IN ENGLISH - Шепітько, В.І.; Yakushko, O.S.; Yeroshenko, G.A.; Lysachenko, O.D. (World of Medicine and Biology, 2012)
Combining different methods of teaching new material, using new visual aids, the activation of self extracurricular work improve the quality of the obtained student’s knowledges.
Keywords: histology; foreign students; lectures; practical classis; self-studied work